Improving The Competency of Elementary's Teachers at Cileungsi in Preparing Merdeka Belajar Lesson Plan (RPP) Based on Characters and 21st Century Skills - Lia Marliana, N.; Suntari, Yustia; Utami, Sintowati Rini; Oktaviani, Reni (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2021)
This Community Service Activity (P2M) departs from the problems of teachers' ignorance of the concept of the Merdekan Belajar’s Curriculum and its implementation. This P2M activity aims to improve the competence of elementary school teachers in Cinyosog Village, Cileungsi in compiling a Learning Implementation Plan (RPP) for Merdeka Belajar based on characters and 21st century skills. This competency enhancement was carried out through socialization activities regarding RPP Merdeka Belajar based on characters and 21st century skills, then Training on Preparation for the Merdeka Belajar’s RPP based on the Character and Skill of 21st Century for Teachers of SDN 01 Cinyosog by offline and online. This P2M activity was attended by 14 teachers at SDN Cinyosog 01 Cileungsi. This training provided the concept of Merdeka Belajar based on characters and 21st century skills, then compiled RPP. This RPP is linked to the 2013 SD Curriculum that was applicable during the Covid-19 pandemic, namely the Merdeka Belajar’s RPP with simplification of KI-KD in the curriculum structure, as well as simplifying the components in the RPP. The lesson plan includes three components, namely learning objectives, learning steps, and evaluation of the learning presented based on the characters and skills of the 21st century. The product of this training activity is a collection of lesson plans compiled by the teachers of SDN Cinyosog 01 Cileungsi and videos of the training activities for the Merdeka Belajar’s RPP based on the Characters and Skills of the 21st Century which was uploaded on the Youtube channel of the PBSI FBS UNJ Study Program.